An Investigation of the Influence of Psychological Contract Violation on Organisational Commitment, Job Satisfaction, and Absenteeism among Chinese Business Graduates in Their First Employment - Jiang, Yu (2009)
The research aim of this research is primarily to provide an insight into the effects of psychological contract violation on the three mentioned attitudinal and behavioural outcomes to work by business graduates in China during their first employment, so that responsive findings may not only help to enrich the theories related to psychological contract through putting into the context of business graduates in China, but also may aid in providing managerial implications to managers in organisations in China how to effectively manage psychological contract in order to avoid or reduce the adverse affect of psychological contract violation so that talented workers can be usefully retained. The findings of the research suggested that the conceptual understanding of psychological contract support the concept it is an exchange of obligations of employees rather than organisation. The content of psychological contract appears to be transactional contract among business graduates in China since their job role is predominantly administrative. This research finds that distributive justice can also lead to continuance commitment. It is not significant that violation is associated with absenteeism.